2021
DOI: 10.3390/e23040457
|View full text |Cite
|
Sign up to set email alerts
|

Research on Channel Selection and Multi-Feature Fusion of EEG Signals for Mental Fatigue Detection

Abstract: With the rapid development of modern social science and technology, the pace of life is getting faster, and brain fatigue has become a sub-health state that seriously affects the normal life of people. Electroencephalogram (EEG) signals reflect changes in the central nervous system. Using EEG signals to assess mental fatigue is a research hotspot in related fields. Most existing fatigue detection methods are time-consuming or don’t achieve satisfactory results due to insufficient features extracted from EEG si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Fourth, since one of the objectives of this study is to use minimal EEG signal channels, it is necessary to identify the active electrodes to reduce the computational complexity. In accordance with [24,25,58,59], 12 electrodes, out of the…”
Section: Preprocessingmentioning
confidence: 94%
See 1 more Smart Citation
“…Fourth, since one of the objectives of this study is to use minimal EEG signal channels, it is necessary to identify the active electrodes to reduce the computational complexity. In accordance with [24,25,58,59], 12 electrodes, out of the…”
Section: Preprocessingmentioning
confidence: 94%
“…Fourth, since one of the objectives of this study is to use minimal EEG signal channels, it is necessary to identify the active electrodes to reduce the computational complexity. In accordance with [24,25,58,59], 12 electrodes, out of the 30 electrodes used for signal recording, were identified in the form of six active regions, on the basis of the electrode weights, for this purpose. Accordingly, only data from the 12 selected channels were used for the compression and data processing, and the rest of the channels were excluded from the processing.…”
Section: Preprocessingmentioning
confidence: 99%
“…In a similar manner, we asked participants to complete a second CFS scale in 5 min to confirm their level of fatigue. Our previous studies [20] have demonstrated that the EEGs collected under both conditions represent both states of alertness and fatigue, as prior to the 2-back experiment, subjects' CFS scores were all less than 4, whereas after approximately 75 min of testing, subjects' CFS scores were all greater than 4 and a oneway analysis of variance (ANOVA) of the two score profiles yielded p = 5.42 × 10 −10 , implying that the scores for these two states were completely different. This is consistent with the experimentally recorded performance of the subjects on the 2-Back task: subjects gradually became fatigued as they completed the 2-Back task, taking longer to respond to the stimuli in order to resist the effects of fatigue, and the accuracy of task completion decreased as the experiment progressed.…”
Section: Self-designed Datasetmentioning
confidence: 97%
“…EEG data is commonly broken down into several rhythmic signals according to different frequency bands and these rhythmic signals alterations are analyzed when mental fatigue builds up. EEG signals typically contains the delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13)(14), beta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-50 Hz) bands, each of which has a functional significance and is a reflection of various cognitive behavioral and physiological activities of the human brain [2]. Many studies show that the EEG is sensitive to fluctuations in mental alertness and that the persistence of mental fatigue is highly correlated with changes in EEG rhythms [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to other papers as [ 33 ] that presents a new method for EEG channel selection optimisation based on relief function [ 34 ], the proposed approach aims to realise a data-driven procedure, considering every feature highly affected by channel selection and avoiding calculating the summation of features weight of each channel as in [ 33 ], in order to increase the accuracy performance.…”
Section: Introductionmentioning
confidence: 99%